REKONSTRUKSI MAQÂSID AL-SYARÎ‘AH DALAM PARADIGMA FIQH NEGARA-BANGSA - Rahayu Rahayu (IAIN Langsa, 2016)
Basically there is no contradiction between Islamic law and Human Rights (HAM). Because the purpose of Islamic law is to realize the favor of human life, which includes basic human needs. The problem is, the formulation of maqasid sharia which is called by al-Ghazali as a real favor, in addition, maqasid al-khalq or maslahah gharîbah currently still not accommodate the basic needs of people who live in the nation-state system, it is tend to give the favor to individual oriented (fardiyyah). While the nation-state paradigm is more oriented towards the realization of public benefit (ijtima'iyyah). In ijtihad fiqh nation state, maqasid al-syar'iah as a value ​​that guide the process of reasoning, because it is the final movement (al-'illah al-ghâiyyah). By making maqasid sharia as a value, it will affect a shift paradigm maqasid sharia from the principles of protection which tends to maintain the minimum boundaries to become a necessity for the values of fundamental, which is oriented towards to realize a favor maximally